Clinical and Microbiological Efficacy of Adjunctive Systemic Quinolones to Mechanical Therapy in Periodontitis: A Systematic Review of the Literature - Carlos-M. Ardila; Jader-Alexander Bedoya-García (International Journal of Dentistry)
Objectives. To assess the clinical and microbiological efficacy of systemic quinolones adjunctive to mechanical therapy in periodontitis patients. Materials and Methods. A systematic review of the scientific literature was carried out. The search scheme comprised the Scopus, PubMed/MEDLINE, SCIELO (Scientific Electronic Library Online), and LILACS (Literatura Latinoamericana y del Caribe en Ciencias de la Salud) databases, together with the gray literature. MeSH terms and keywords were utilized to explore publications in all idioms. Only randomized clinical trials (RCTs) that met the selection criteria were included. Results. A total of 4 RCTs were selected. These RCTs found superior clinical and microbiological efficacy of adjunctive systemic moxifloxacin (MOX) and levofloxacin (LV) compared to subgingival debridement plus placebo. Improvements in PD and CAL were 2.4 ± 0.8 mm and 2.7 ± 0.9 mm for LV, and 1.5 ± 0.5 mm and 1.8 ± 0.5 mm for MOX, respectively. After six months of follow-up, adjunctive MOX reduced the presence of Aggregatibacter actinomycetemcomitans to imperceptible levels, while LV markedly reduced this microorganism. Some adverse events were reported in the LV group and none in the MOX group. Conclusions. Adjunctive MOX and LV improve probing depth and clinical attachment level compared with subgingival debridement alone in patients with periodontitis. The efficacy of these quinolones against A. actinomycetemcomitans was also superior.